Analisis Nilai Pendidikan Karakter dalam Kumpulan Cerpen Cahaya-Cahaya Kecil Karya Hasta Indriyana dan Relevansinya Dengan Profil Pelajar Pancasila - Abdillah Abbas, Zainul; Widayati, Mukti; Suwarto, Suwarto (Jayapangus Press, 2025)
Character education in elementary schools is crucial in shaping a generation with integrity. However, weak implementation, bullying, and gadget addiction hinder these efforts early on. These challenges highlight the need to integrate character values into learning through effective and engaging methods. This study aims to examine three main aspects: (1) describe the character education values in the short story collection Cahaya-Cahaya Kecil by Hasta Indriyana, (2) describe their relevance to the dimensions of the Pancasila Student Profile, and (3) formulate short story-based learning strategies for elementary schools. This research uses a descriptive qualitative method with a literary sociology approach. The analysis technique used is content analysis to identify character values in short stories and dialectical analysis to connect them with social reality. Data were analyzed using the Miles & Huberman model, which includes data collection, reduction, and presentation. Validation was conducted through source triangulation by comparing various primary data and confirming them with relevant theories and method triangulation by using various analysis techniques to ensure consistency of findings. The results show that this short story contains various character education values. These values have relevance to the Pancasila Student Profile because they reflect moral and social principles that are aligned with national education goals. This research also formulates short story-based learning strategies that include group discussions, creative projects, reflection, and authentic assessment. The findings confirm that short stories are an effective medium in character education and have the potential to be applied in learning to optimally support the Pancasila Student Profile.